Stakeholders' viewpoints on work-integrated learning practices in radiography training in South Africa: Towards improvement of practice. Issue 1 (February 2019) - du Plessis, J.
Abstract: Purpose: The aim of this investigation was to suggest practices to improve the delivery of work-integrated learning (WIL) in radiography training in South Africa (SA). Methods: An extensive survey was conducted among all universities in SA involved in the training of radiography students, to investigate the current delivery of WIL. Data were collected by means of quantitative questionnaires with open-ended qualitative components. The questionnaire was distributed to lecturers (n = 32), clinical supervisors (n = 44) and final-year students in Radiography (n = 146). Results: The quantitative (closed questions) and qualitative (open-ended comments) findings from the stakeholders with regard to the improvement of practice in the delivery of WIL in radiography training are presented in this article. The main themes discussed relate to curriculum design for WIL, teaching/learning of WIL, assessment of WIL and management and coordination of WIL. Conclusion: WIL is a powerful pedagogy if implemented and managed correctly. The results from this study may enable lecturers in radiography programmes in SA to improve the delivery of WIL in the training of high quality, employable graduates. Highlights: Work-integrated learning (WIL) has to be implemented and managed properly to ensure its success. Assessment activities and the intended outcomes for WIL need to be aligned. Workplace supervisors require thorough training for their involvement and responsibilities in WIL. Frequent visitation of students by a lecturer at the clinical setting will promote communication between stakeholders.